2012
DOI: 10.2147/clep.s23536
|View full text |Cite
|
Sign up to set email alerts
|

Emergent trends in the reported incidence of prostate cancer in Nigeria

Abstract: BackgroundTo date there has not been any nationwide age-standardized incidence data reported for prostate cancer in Nigeria. We examined and integrated diverse trends in the age-specific incidence of prostate cancer into a comprehensive trend for Nigeria, and examined how best the existing data could generate a countrywide age-standardized incidence rate for the disease.MethodsData were obtained from studies undertaken between 1970 and 2007 in referral hospital-based cancer registries. Records from at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
(63 reference statements)
4
5
0
Order By: Relevance
“…1980–2009, excluding 2010–2015 where we retrieved only 4 data points, see Tables 3 & 4 ). This is also in line with many reports; for example, advancing age has been described as a major risk factor for prostate cancer, with a peak incidence among men aged 65 years or higher across many world regions [ 56 ]. Moreover, in 1990, incidence rates of prostate cancer were between 2.6–16.9/100,000 across many parts of Africa [ 20 , 74 ], with this increasing to 4.7–38.1/100,000 in 2007 [ 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…1980–2009, excluding 2010–2015 where we retrieved only 4 data points, see Tables 3 & 4 ). This is also in line with many reports; for example, advancing age has been described as a major risk factor for prostate cancer, with a peak incidence among men aged 65 years or higher across many world regions [ 56 ]. Moreover, in 1990, incidence rates of prostate cancer were between 2.6–16.9/100,000 across many parts of Africa [ 20 , 74 ], with this increasing to 4.7–38.1/100,000 in 2007 [ 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of CaP was highest among patients older than seventy-two years. This is consistent with studies of (Ifere, Abebe, & Ananaba, 2012). CaP is known to be a disease of the aged with very few incidences observed among those below forty years, and very recurring as men progress in age.…”
Section: Discussionsupporting
confidence: 91%
“…However, a prevalence rate as high as 15.7% of the disease was documented recently in a population-based study reported from the Eastern part of Nigeria [4]. There are also various reports suggestive that the PCa disease is occurring among the younger Nigerian males in contrast to previous reports [5].…”
Section: Introductionmentioning
confidence: 96%